Let's Connect to Keep the Distance: How SMEs Leverage Information and Communication Technologies to Address the COVID-19 Crisis - Charlotte Wendt; Martin Adam; Alexander Benlian; Sascha Kraus (Information Systems Frontiers, 2021)
COVID-19 caused significant challenges for small and medium-sized enterprises (SMEs) in the event industry. To address these challenges, many SMEs leveraged information and communication technologies (ICTs), with some even emerging strengthened from the crisis. Drawing on the technology-organization-environment framework and technology-affordances-and-constraints theory, we investigate the adoption of ICTs as a crisis response strategy in 10 SMEs in the German business event (e.g., corporate events, conferences) industry. Our findings reveal that ICT adoption not only depends on rational decisions based on organizational, environmental, and technological characteristics, but also on these dimensions' interrelationship and the specific ICTs' affordances and constraints. Introducing readily available ICTs (e.g., video-conferencing) has significant potential in addressing physical distancing in the short and medium term, while more sophisticated ICTs (e.g., virtual reality) are more likely to gain importance in the long term. Thus, we expand our understanding of organizational technology adoption and ICT-enabled crisis response strategies in SMEs.
Keywords: 000; Technology-organization-environment framework; Technology-affordances-and-constraints theory; Information and communication technologies; SME; Crisis response; COVID-19